Isolation and Antibacterial Activity Test of Lactid Acid Bacteria (LAB) from Pliek U and Pliek U Oil (Minyeuk Brok) - C Yulvizar; Y S Ismail; Amalina; S Mahzura; S A Zazila; A Haq; Fahrinnisa (Postgraduate, University of Mataram, 2026)
Lactic Acid Bacteria (LAB) are a group of microorganisms that play a crucial role in the fermentation of various traditional foods. The presence of LAB in fermented food results in the production of various types of metabolite compounds that can act as antimicrobials. The objective of this study is to isolate and characterise LAB from pliek u and pliek u oil (minyeuk brok), and to determine their potential antibacterial activity against Staphylococcus aureus and Escherichia coli. The disc diffusion method was used to test the antibacterial activity. The results showed two LAB isolates from pliek u (IPU2 and IPU7) and one LAB isolate from pliek u oil (minyeuk brok) (IMP1). The colonies are cream-coloured, cocci in shape, with smooth edges and a raised elevation. The cells exhibit Gram-positive cocci and bacilli. Isolate IPU2 has the largest average inhibition zone diameter against Staphylococcus aureus (6.35 mm) but does not inhibit the growth of Escherichia coli.